Reproductive dysfunction in women with epilepsy: recommendations for evaluation and management. Issue 2 (1st August 2002) - Bauer, J; Isojärvi, J I T; Herzog, A G; Reuber, M; Polson, D; Taubøll, E; Genton, P; van der Ven, H; Roesing, B; Luef, G J; Galimberti, C A; van Parys, J; et al.
Abstract : Background: Epilepsy is commonly associated with reproductive endocrine disorders. These include polycystic ovary syndrome (PCOS), isolated components of this syndrome such as polycystic ovaries, hyperandrogenaemia, hypothalamic amenorrhoea, and functional hyperprolactinaemia. Objective: To summarise the currently known relations between epilepsy and reproductive endocrine disorders. Methods: A review of clinical experience and published reports. Results: The most likely explanations for endocrine disorders related to epilepsy or antiepileptic drugs are: (1) a direct influence of the epileptogenic lesion, epilepsy, or antiepileptic drugs on the endocrine control centres in the brain; (2) the effects of antiepileptic drugs on peripheral endocrine glands; (3) the effects of antiepileptic drugs on the metabolism of hormones and binding proteins; and (4) secondary endocrine complications of antiepileptic drug related weight changes or changes of insulin sensitivity. Regular monitoring of reproductive function at visits is recommended, including questioning about menstrual disorders, fertility, weight, hirsutism, and galactorrhoea. Particular attention should be paid to patients on valproate and obese patients or those experiencing significant weight gain. Single abnormal laboratory or imaging findings without symptoms may not constitute a clinically relevant endocrine disorder. However, patients with these kinds of abnormalities should be monitored to detect the possible development of a symptomatic disorder associated with, for example, menstrual disorders or fertility problems. Conclusions: If a reproductive endocrine disorder is found, antiepileptic drug treatment should be reviewed to ensure that it is correct for the particular seizure type and that it is not contributing to the endocrine problem. The possible benefits of a change in treatment must be balanced against seizure control and the cumulative side effect of alternative agents.